Introduction: Exploring the Scope of the Australian Indigenous Studies Learning and Teaching Network - Barney, Katelyn; Shannon, Cindy; Nakata, Martin (The Australian Journal of Indigenous Education, 2014)
The Australian Indigenous Studies Learning and Teaching Network was established in 2011 to develop a focused national network of scholars to engage in key discussions about teaching Indigenous Studies at tertiary level. Funded by the Office for Learning and Teaching (2011–14), the Network combines leaders and early career academics and builds relationships between scholars in the discipline, identifies key issues and explores effective teaching and learning approaches. This introductory essay places this Special Issue of The Australian Journal of Indigenous Education (AJIE) in context by exploring the aims and outcomes of the Network along with the positioning of the Network team. It also examines key challenges for the Network and possible future directions.